Coffee Tourism Development Strategy for Potential Liberica Coffee Farm in Poncokusumo, Malang Regency - Wafaretta, Erona; Faronny, Danniary Ismail (Directorate of Research and Community Services, 2024)
This research evaluate the potential of developing a coffee tourism strategy focused on the unique Liberica coffee plantations in Poncokusumo, Malang, Indonesia. By highlighting the distinctive sensory profile, Liberica coffee provides an opportunity to differentiate Poncokusumo as a specialized coffee tourism destination. This research will be designing a coffee tourism strategy that can be applied to the Poncokusumo Liberica coffee plantation, Malang. This research uses a robust SWOT analysis to examine the potential strengths, weaknesses, opportunities, and threats associated with leveraging Liberica coffee for tourism based on cupping score and perception panelist. The findings underscore the critical role of sustainable agricultural practices in enhancing economic benefits while conserving local ecosystems. This research highlights the importance of aggressive strategies that can be carried out for this location aligning tourism initiatives with local cultural and ecological contexts to ensure long-term success. Educational tourism can be implemented in the Jajang Hamlet coffee plantation, Poncokusumo District, or outside the coffee plantation by collaborating with coffee shops or coffee shops in Malang. Through educational tourism, tourists will deeper their knowledge and increase their interest in liberica coffee; in addition, interactive classes can also improve skills and understanding of liberica coffee.